Ventriculoperitoneal Shunt with Communicating Peritoneal & Subcutaneous Pseudocysts Formation - Alduraibi, Sharifa (International Journal of Health Sciences, 2014)
<!–[if gte mso 9]> <![endif]–> Â Â A case of cerebrospinal fluid (CSF) pseudocysts in a patient with a ventriculoperitoneal (VP) shunt is reported to describeacute unusual location of developmentof pseudocyst. Â Â Â In the setting of a VP shunt, the frequency of abdominal CSF pseudocyst formation is approximately 4.5%, often being precipitated by a recent inflammatory / infective process or recent surgery. Â Â Larger pseudocysts tend to be sterile, whereas smaller or multiloculated pseudocysts are more often infected. Computed tomography (CT) and ultrasound (US) has characteristic findings. Â Â This is an uncommon presentation of VP shunt with no evidence of infection. The objective of this case report is to create awareness about imaging findings of complications of VP shunt at an unusual location. Â <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>